Gene therapies for high-grade gliomas: from the bench to the bedside - Giotta Lucifero , Alice; Luzzi, Sabino; Brambilla, Ilaria; Guarracino, Carmen; Mosconi, Mario; Foiadelli, Thomas; Savasta, Salvatore (Acta Biomedica Atenei Parmensis, 2020)
Background: Gene therapy is the most attractive therapeutic approach against high-grade gliomas (HGGs). This is because of its theoretical capability to rework gene makeup in order to yield oncolytic effects. However, some factors still limit the upgrade of these therapies at a clinical level of evidence. We report an overview of glioblastoma gene therapies, mainly focused on the rationale, classification, advances and translational challenges. Methods: An extensive review of the online literature on gene therapy for HGGs was carried out. The PubMed/MEDLINE and ClinicalTrials.gov websites were the main sources. Articles in English published in the last five years were sorted according to the best match with the multiple relevant keywords chosen. A descriptive analysis of the clinical trials was also reported. Results: A total of 85 articles and 45 clinical trials were selected. The main types of gene therapies are the suicide gene, tumor suppressor gene, immunomodulatory gene and oncolytic therapies (virotherapies). The transfer of genetic material entails replication-deficient and replication-competent oncolytic viruses and nanoparticles, such as liposomes and cationic polymers, each of them having advantages and drawbacks. Forty-eight clinical trials were collected, mostly phase I/II. Conclusion: Gene therapies constitute a promising approach against HGGs. The selection of new and more effective target genes, the implementation of gene-delivery vectors capable of greater and safer spreading capacity, and the optimization of the administration routes constitute the main translational challenges of this approach.